Increasing the survival of transverse rectus abdominis musculocutaneous flaps with a Botulinum toxin-A injection: A comparison of surgical and chemical flap delay methods. Issue 7 (July 2016) - Temiz, Gökhan; Yeşiloğlu, Nebil; Şirinoğlu, Hakan; Akpınar, Ali Cem; Sarıcı, Murat; Filinte, Deniz; Filinte, Gaye Taylan; Bozkurt, Mehmet
Summary: Background: Botulinum toxin type-A (Bot-A) is a commonly used drug for both cosmetic and therapeutic purposes. The effects of Bot-A on skin and muscle flaps and the related mechanisms have been described previously. In this study, we used a rat transverse rectus abdominis musculocutaneous (TRAM) flap model to examine the effects of Bot-A on the skin island, which is perfused by the rectus abdominis muscle according to the angiosome concept. Methods: Forty female rats were divided into five groups, including control and sham groups. In the control group, a TRAM flap was raised and sutured back after inserting a silicone sheath underneath the flap. In the sham group, the flap was raised 1 month after injecting saline into the muscle. In the chemical delay group, the flap was raised 1 month after injecting 10 IU of Bot-A. In the surgical delay group, the flap was raised 2 weeks after ligating the cranial epigastric artery. In the surgical and chemical delay group, a Bot-A injection was performed initially, a cranial epigastric artery was ligated after 2 weeks, and a TRAM flap was raised after the first month. In all groups, laser Doppler examination, photographic documentation, and analysis of the flap survival rates were performed. In the histopathological evaluation, the diameter measurements of the caudal epigastric vessels, vascular density measurements using CD31 stain, and apoptotic rate estimation using the Tunnel method were performed. Results: The necrosis ratios, arterial cross-sectional diameters, and microvascular density measurements were significantly superior compared to those of control and sham groups; however, there was no significant difference between the delay groups. There was also no difference in the laser Doppler measurements between the groups and the zones of the TRAM flaps. Conclusion: An injection of Bot-A increases muscular circulation and flap survival of TRAM flaps in rats.